2009
DOI: 10.1007/s11434-009-0631-3
|View full text |Cite
|
Sign up to set email alerts
|

Embryo implantation: A time for recalling and forwarding

Abstract: The success of embryo implantation is a critical step towards further embryo development and pregnancy outcome. The observations and investigations on embryo implantation have been over a century. A huge body of knowledge has been accumulated in anatomy, histology, ultrastructure and hormonal regulation; as well as recently in depth information about molecular signaling pathways got from studies of genomic wide gene screening and specific gene deletion. The knowledge from basic research has also substantially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…18 If the condition of maternal uterus was disturbed, the loss of embryos would happen. 19 In our previous studies, CS 2 exposure at peri-implantation disturbed expression of MMP(metalloproteinase)-2, MMP-9, 20 leukemia inhibitory factor, 21 adhesion molecule fibronectin and its ligand, and integrin β1 in the uterus of gestational mice, 22 all these are related to implantation failure. Therefore, we speculated that CS 2 exposure might affect the environment of the uterus and disturb the development of the implantation window to disturb the process of embryo implantation.…”
Section: Discussionmentioning
confidence: 92%
“…18 If the condition of maternal uterus was disturbed, the loss of embryos would happen. 19 In our previous studies, CS 2 exposure at peri-implantation disturbed expression of MMP(metalloproteinase)-2, MMP-9, 20 leukemia inhibitory factor, 21 adhesion molecule fibronectin and its ligand, and integrin β1 in the uterus of gestational mice, 22 all these are related to implantation failure. Therefore, we speculated that CS 2 exposure might affect the environment of the uterus and disturb the development of the implantation window to disturb the process of embryo implantation.…”
Section: Discussionmentioning
confidence: 92%
“…Estrogen and progesterone regulate the expression of VGEF and their receptor on embryo preimplantation in various ways, and then uterine vascular permeability and angiogenesis were influenced. Progesterone participated in positive regulation of expression of HOXa-10 in uterine stroma [8,14].…”
Section: Discussionmentioning
confidence: 99%
“…AKT, Wnt, SOX), regulates not only the embryogenesis but also the subsequent embryo migration, adhesion and development (20,21). Previous studies have suggested that embryos, via EMT activation, may influence endometrial receptivity too (22)(23)(24). In particular, it has been shown that human blastocyst before to implant releases, in vitro, soluble factors that differentially modify human endometrial epithelial cell adhesion and EMT gene expression (15,25).…”
Section: Mechanisms Regulating the Embryo Endometrial Cross-talkmentioning
confidence: 99%